2022
DOI: 10.1039/d1tc04930e
|View full text |Cite
|
Sign up to set email alerts
|

A scintillating nanoplatform with upconversion function for the synergy of radiation and photodynamic therapies for deep tumors

Abstract: Collaborative therapy is regarded as an effective approach in lifting the therapeutic efficacy of cancer. In this work we have proposed and validated the concept of upconversion lumienscence image guided...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…859,860 Phototherapy as an emerging method, holds the advantage of noninvasiveness, while it is limited by penetration. [861][862][863] During these decades, researchers have exploited various sorts of ingenious combinations to bring their superiority into full play and overcome their deficiency. The combinations are mainly divided into the below three aspects.…”
Section: Nps For Radiophototherapymentioning
confidence: 99%
“…859,860 Phototherapy as an emerging method, holds the advantage of noninvasiveness, while it is limited by penetration. [861][862][863] During these decades, researchers have exploited various sorts of ingenious combinations to bring their superiority into full play and overcome their deficiency. The combinations are mainly divided into the below three aspects.…”
Section: Nps For Radiophototherapymentioning
confidence: 99%
“…Poly(ethylene) glycol (PEG) is a general nanoparticle surface modification for extending circulation times of nanoparticles in vivo by reducing protein adsorption and lowering interactions of PEGylated nanomaterials with organs and cells of the mononuclear phagocyte system. [80,84,92] However, recent studies have shown the potential for PEG coatings to cause unwanted immune side effects. As the details of PEG-mediated toxicity are outside the scope of this article, the authors recommend a review that was recently published by our research group covering PEG-mediated nanoparticle toxicity and other potential toxic effects of nanoparticles in animals and humans.…”
Section: Biocompatibility and Biodistributionmentioning
confidence: 99%
“…From this perspective, X-PDT can also be considered a radiation-resistant radiosensitization method. 57–61…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, X-PDT can also be considered a radiation-resistant radiosensitization method. [57][58][59][60][61] The idea of combining the deep penetration of X-rays and the specific targeting of phototherapy was first proposed by Chen et al in 2006, and since then, the field has grown exponentially. [62][63][64][65][66] However, X-rays cannot directly excite PSs to produce ROS due to the mismatch between the energy gap of most PSs and X-rays.…”
Section: Introductionmentioning
confidence: 99%